INTEGRATING TECHNICAL, VALUE AND RELATIONAL PERSPECTIVES IN URBAN REGENERATION PROJECTS: A FRAMEWORK FOR THE MUNICIPALITY OF KISELA VODA, SKOPJE - Isabella M. Lami; Elena Todella; Alessandro Armando; Ognen Marina (Valori e Valutazioni)
Sustainable and resilient urban regeneration encompasses the transformation of areas or buildings and their neighbourhoods, involving issues with recognised environmental, economic and social implications. In particular, cities can support the creation of new and multiple values through the transformation of the built environment, having a high concentration of capital and resources distributed over a limited territory. This paper analyses the role that design can play in pursuing sustainable cities, focusing the discussion on how to promote urban regeneration paths through urban, architectural and landscape projects. The transformation of the Municipality of Kisela Voda in Skopje, the capital of North Macedonia, is proposed as a case study, as an ongoing transformation process object of a recently concluded competition for the sustainable urbanization of the neighbourhood. The analysis is conducted through a series of district plans and projects developed within the framework of the “Architecture and Urban Space” master’s degree course at Politecnico di Torino, focusing on a threefold performativity of the projects, which act through: (i) mapping, with a recomposition of the conditions of “engagement”; (ii) explicating, through the sharing of the implications of value creation; (iii) translating, with facilitation of relations between actors.